Factors associated with suitability of empiric antibiotic therapy in hospitalized patients with bloodstream infections. (4th May 2017) - Grossman, Chagai; Keller, Nathan; Bornstein, Gil; Ben-Zvi, Ilan; Koren-Morag, Nira; Rahav, Galia
Abstract : Background: Bacteremia is associated with high morbidity and mortality rates. Initiation of inadequate empiric antibiotic therapy is associated with a worse outcome. The aim of this study was to establish the prevalence and the factors associated with inappropriate empiric antibiotic therapy in patients hospitalized with bacteremia. Methods: A cross-sectional study was conducted during January 2010–December 2011 at the medical wards of the Chaim Sheba Medical Center, Israel. The records of all patients with bacteremia were reviewed. Clinical and laboratory characteristics, bacteremic pathogens and antimicrobial agents were retrieved from the medical records. Factors associated with appropriateness of empiric antibiotic therapy were assessed. Results: A total of 681 eligible adults were included in the study. Antibiotic therapy was found to be inappropriate in 138 (20.2%) patients (95% C.I. 17.2–23.2). The rate of appropriateness was not related to the type of antibiotic regimen and the type of bacteria. Patients with healthcare-associated infections were more likely to be administrated inappropriate antibiotic therapy. Patients with primary bloodstream infections were also more likely to be administrated inappropriate antibiotic therapy. Empiric combination therapy was more likely to be appropriate than monotherapy, except for an aminoglycosides-based combination. Conclusions: Combination empiric antibiotic therapy should be considered in patients with healthcare-associated infections and in those with primary bloodstream infections.